Spending instructional time wisely: Using brief intervention probes to determine the most effective reading fluency strategy - Casey, Laura; Robertson, Janet; Williamson, Robert; Serio, Constance; Elswick, Susan (Canadian Journal of Education/Revue canadienne de l'éducation, 2011)
Single case studies are helpful in analyzing the details of implementation of an individualized intervention program (reference). Their exploratory nature can result in more case studies, which can be compared to allow for better understanding of an intervention's usefulness. This case study investigated the effectiveness of using brief intervention probes for two different evidence-based interventions to identify the most effective teaching strategy for a struggling elementary school reader. Following initial grade level placement, two intervention probes were tested by rapidly switching between them, then analyzing the data. The intervention that yielded the most gains in words correctly read (WCPM) was selected and implemented to increase the likelihood for success. Results were promising as WCPM increased by 37 words from baseline to intervention. The study provides a glimpse into a much-needed area of research regarding using brief intervention probes to determine the most effective specific interventions prior to implementation. This research provides recommendations for use within any intervention model, especially Response to Intervention.